PELAKSANAAN PEMBERIAN KEWAJIBAN NAFKAH TERHADAP ANAK AKIBAT TERJADINYA PERCERAIAN - Prasetyo, Andreas Henriko (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTÂ Marriage breakdown due to divorce according to article 149 Compilation of Islamic Law has its own legal consequences for the husband, namely the emergence of obligations after dropping divorce against his wife, among others by giving muth'ah to cheer up ex-wives, providing income during the period of iddah, paying off dowry pay for their children. Writing this thesis uses a method with a normative juridical type. With the problem approach used by the author is to use the Law Approach and Conceptual Approach. Legal materials used are primary legal materials, secondary legal materials and non-legal materials The problem statement of this thesis is to know and understand the Parents' Responsibilities to Children after Divorce; to know and understand the judge's rationale (ratio decidendi) in granting the Decision reconciliation request.Furthermore, from the results of research and drawing conclusions in the form of arguments. After the breakup of a marriage, it will have legal consequences for both parties and their children. For a husband it is an obligation, for his ex-wife and children to be a right. Divorced parents still have an obligation to provide for their children, this is regulated in Article 149 letter (d) Compilation of Islamic Law.Keywords: LEGACY OF CHILDREN DUE TO THE EXPERIMENT OF THE RELIGION.